A Model-driven Architecture for Multi-protocol OBD Emulator - Rosado, Fernando Jorge Varandas Anão (2017)
The Internet of Things (IoT) might be the next revolutionary technology to mark a generation. It could have a particularly strong influence on the automotive industry, changing people’s perception of what a vehicle can do. By connecting several things in a car, IoT empowers it to sense and communicate. Furthermore, this technology clearly opens the way to emerging applications such as automated driving, Vehicle-to-Vehicle and Vehicleto-Infrastructure communication. Vehicle’s information about its environment and surroundings is crucial to the development of existing and emerging applications. It is already possible to communicate directly (on-site) with vehicles through a built-in On Board Diagnostics (OBD), making it possible to obtain crucial information about the state of the vehicle in real environments. However, there is zero tolerance for error when developing new applications for vehicles that are, a priori, extremely costly and that must also safeguard human lives. Therefore, there is an increasing need for OBD emulators which can allow the development of new applications. This Thesis proposes a model-driven architecture for multi-protocol OBD emulator, encouraging the development of new emerging OBD systems in a safety environment, to promote the creation of applications to interact or use vehicles’ data. In this sense, the addressed specifications are: Less expensive comparing with today’s solutions; Compatible with different OBD protocols communication; Open Source Hardware and Software suitable for Do-It-Yourself (DIY) development.